Reconceptualizing Financial Management in the Age of FinTech 4.0: Efficiency, Inclusion, and Financial Resilience - Muhammad Haris Saputra; Kurnia Permana; Try Syeftiani (International Journal of Business and Quality Research, 2025)
The rapid development of financial technology (FinTech) has fundamentally transformed financial management practices across organizations and economic systems worldwide. The emergence of FinTech 4.0 characterized by the integration of artificial intelligence, big data analytics, blockchain technology, cloud computing, and open finance has shifted financial management from a traditional administrative function toward a strategic driver of efficiency, financial inclusion, and financial resilience. In recent years, increasing economic uncertainty, technological disruption, and global financial shocks have intensified the need for adaptive and resilient financial management systems. This study aims to systematically review and synthesize recent international literature on the transformation of financial management in the era of FinTech 4.0, with a particular focus on three interrelated dimensions: efficiency, financial inclusion, and financial resilience. Using a structured literature review approach, this study analyzes peer-reviewed journal articles published between 2020 and 2025 that examine the role of FinTech in reshaping financial management practices across different organizational and institutional contexts. The findings indicate that FinTech significantly enhances financial management efficiency through automation, real-time data processing, and advanced analytics. Furthermore, FinTech expands financial inclusion by reducing access barriers to financial services for individuals and small and medium-sized enterprises. In addition, FinTech strengthens financial resilience by enabling proactive risk management, predictive financial planning, and adaptive decision-making during periods of economic disruption. By integrating these three dimensions within a unified analytical framework, this study contributes to the literature by offering a comprehensive understanding of FinTech-driven financial management transformation and providing insights for practitioners, policymakers, and researchers.